Pineapple pomace powder (freeze-dried): Effect on the texture and rheological properties of set-type yogurt. (October 2022) - Meena, L.; Neog, Rooman; Yashini, M.; Sunil, C.K.
Highlights: Freeze dried pineapple pomace is rich in fiber and carbohydrate contents and low in fat content. Physicochemical and functional properties of pineapple pomace showed the possible utilization of pomace as a fiber enhancing ingredient in the yogurt. Yogurt added with 0.25% PP exhibited the most stable structure over a 15 days storage period compared to the other samples. Abstract: Pineapple pomace is the waste produced during the processing of pineapple. Functional foods are growing enormous and attracted by consumers. Taking this into consideration, pomace incorporated yogurt was developed and its textural and rheological properties were evaluated during the long-term refrigerated storage of the product. The powder was found to have high levels of fiber (51%) and carbohydrate (31.24%) and low levels of fat (2.16%) and protein (4.88%) which pointed to its utilization as a fiber enhancing ingredient in the yogurt, which is a low fiber food. The pomace was added in different concentrations (0%, 0.1%, 0.25% & 0.5%) and the effect on the physicochemical, textural, and rheological properties of set-type yogurt during storage (15 days) was studied. The texture parameters, firmness, consistency, and cohesiveness had a significant variation ( p < 0.05) over the storage period, indicating reinforcement of the yogurt structure. Similarly, significant variations in pH, syneresis, and titratable acidity were observed for yogurt added with pineapple pomace (PP) when compared to control. Yogurt with PP added showed an inverse relationship between pH and titratable acidity during storage. Also, the viscosity of yogurt decreased with the increase in the concentration of PP and a rheological study pointed out the behavior of yogurt as shear-thinning. Sensory analysis at PP concentrations of 0, 0.1, and 0.25% showed good acceptability compared to 0.5%. This study confirmed the possible utilization of PP as a novel food ingredient and also this valorization technique has great potential in reducing pineapple cannery waste. Graphical abstract: Image, graphical abstract